Reflecting on supervision experiences: Honours students' research projects in development studies at the nelson Mandela University - Mhlahlo, A. (South African Journal of Higher Education, 2020)
This article reflects on my supervision experience of students conducting their one-year research projects at Honours level in the Department of Development Studies at Nelson Mandela University from 2016 to 2018. My conclusion is that students who are enrolled in the block-release1 learning program do not have adequate face-to-face access to various university support systems, such as group work sessions with fellow research students on campus or close to it, regular meetings with supervisors, and research-related workshops. This contributes to students’ feeling of loneliness and exclusion from the university community. As supervisors, we are guilty sometimes, of not encouraging our students to enter the research community by publishing research papers, as they progress towards finishing their research projects. This article proposes strategies to overcome the identified challenges and to exploit emerging opportunities, in order to improve the research supervision practice. The intention of this study is to contribute to the field of teaching and learning in the South African higher education sector, by proposing strategies to improve the practice of research supervision.